Membangun Desa Sendang Sebagai Desa Berkelanjutan Berbasis Penguatan Moderasi Beragam Dan Kearifan Lokal - Cahyani, Seftiana Dwi; Solichin, Moh. Badrus; Auliya, Safira Rizki; A, Rama Dona Risqi; Nida, Karima Naufalin; Salam, M Alfa; M, M. Wildan; Rizal, Achmad; Fadhilah, Hery; A, Rohmatus Zakkiyah K; P , Rizky Tiara; Dewi, Ikvina Kurnia; Ardila, Nourma Nur; Janah, Amma Huqot Nur; Adelya, Nandita; Cholifah, Siti Nur (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The implementation of Real Work Lectures (KKN) in Sendang Village aims to support the KKN theme that has been established by the campus, namely